Environmental Remediation from Industrial Waste in Chemistry Education: Recovering Rare Earth Elements from Red Mud Using Eutectic Ionic Liquids - Widyaningsih, Mia; Mudzakir, Ahmad; Riandi, R; Hernani, H; Nandiyanto, Asep Bayu Dani; Supriatna, Asep; Affifah, Isriyanti; Zidny, Robby (Journal of Tropical Chemistry Research and Education, 2026)
This study aims to conduct laboratory experiments designed to improve students' skills and understanding of environmental remediation of Rare Earth Elements (REEs) extraction from red mud, using Eutectic Ionic Liquids (EILs). The research subjects consisted of 15 chemistry education students in Bandung City. The method is pre-experiment with one group pretest-posttest design. With the first research step, students filled in pre-test questions before doing the practicum, then students were directed to carry out laboratory experiments by starting the preparation of drying and smoothing red mud. Furthermore, the preparation of making Betain-Levulinic Acid EILs and extracting red mud using EILs based on predetermined work procedures. And finally, students are asked to write down the results of the practicum on the Practicum Worksheet and students are asked to fill out a post-test. Based on the results of the study found differences in the ability and understanding of student laboratory experiments seen from the pre-test and post-test assessment scores there is a significant difference that it can be stated to have improved learning. The laboratory experiment learning method can provide field practice experience for chemistry education students in supporting the achievement of SDGs point 15, namely terrestrial ecosystems that focus on restoring land degradation.